LEGISLATIVE ENSURING FOR SEED PRODUCTION OF VEGETABLE CROPS IN RUSSIAN FEDERATION (BASED ON PARLIAMENTARY SESSION ON 11 JULY IN 2017) - S. M. Sirota (Овощи России)
The analysis of the national seed market state really showed the high dependence of Russian food security on imported seeds. The government means for supporting the national seed production program undertaken in 2015 by Ministry of Agriculture of RF were very effective and took action as showed the data from ‘Roselkhozcentre’. Thus, the total land area used for seed production in vegetables, melons and gourds was increased by 48% that amounted to 2104.3 ha in 2016, and that was more than in 2015. Moreover, the vegetable and melon seed producers and breeders are worried about the facts of falsification and low quality. The main reason of occurrence of such seeds that are not meeting the variety requirements in the market is an insufficient legislative system and its lack of correspondence to the current seed production, conditions and up-to-date requirements. It is necessary to take urgent measures to revise the current state of legislative system in national seed production program.